2012
DOI: 10.1021/am301824w
|View full text |Cite
|
Sign up to set email alerts
|

Composition-Controlled PtCo Alloy Nanocubes with Tuned Electrocatalytic Activity for Oxygen Reduction

Abstract: Modification of the electronic structure and lattice contraction of Pt alloy nanocatalysts through control over their morphology and composition has been a crucial issue for improving their electrocatalytic oxygen reduction reaction (ORR) activity. In the present work, we synthesized PtCo alloy nanocubes with controlled compositions (Pt(x)Co NCs, x = 2, 3, 5, 7, and 9) by regulating the ratio of surfactants and the amount of Co precursor to elucidate the effect of the composition of nanocatalysts on their ORR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
77
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(85 citation statements)
references
References 54 publications
7
77
0
1
Order By: Relevance
“…Considering the fact that XPS measurement of the core level is very useful to evaluate D-band shifts because of its high correlation with the valence band XPS, [34] the XPS results unambiguously indicate that the D-band centers of the Pt/NC catalysts downshifted compared to that of the Pt/C. As the oxygen binding energy (E OB ) [35,36] the XPS results are in good agreement with those of the electrochemical measurements.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Considering the fact that XPS measurement of the core level is very useful to evaluate D-band shifts because of its high correlation with the valence band XPS, [34] the XPS results unambiguously indicate that the D-band centers of the Pt/NC catalysts downshifted compared to that of the Pt/C. As the oxygen binding energy (E OB ) [35,36] the XPS results are in good agreement with those of the electrochemical measurements.…”
Section: Resultssupporting
confidence: 64%
“…ECSA values of the catalysts were calculated by integrating the charges in the H UPD region of the CVs. [36] Furthermore, the ORR current density of the Pt/NC 2.0 catalyst at 0.9 V after the durability test decreased by only 9 % (from 3.05 to 2.79 mA cm This indicates that enhanced stability could also be achieved by incorporating nitrogen into the Pt/C catalyst. It has been reported that the nitrogen functionalities on the support usually improve the stability of the supported catalyst particles because of the strong interaction between the support and particles.…”
Section: Resultsmentioning
confidence: 95%
“…2∼7 times compared to that of pure Pt. The enhancement factor has been found to depend on various properties of alloy nanoparticles, e.g., composition, 4,[14][15][16] shape (or size), [17][18][19][20][21] and crystal structure. [22][23][24][25][26][27][28][29] For example, the values of j k for Pt-Co alloys showed a maximum at the atomic ratio of Pt/Co = 3.…”
mentioning
confidence: 99%
“…To address these issues, great efforts have been devoted to constructing Pt‐based alloys by introducing a non‐precious metal (M) . Compared with pure Pt, the PtM alloys usually exhibit a higher catalytic activity and stability, and their enhanced performance is generally attributed to the synergetic effects of electronic (Pt d ‐band vacancy) and geometric (Pt lattice strain) structure modulation, which can alter Pt d ‐band center …”
Section: Introductionmentioning
confidence: 99%